Pengaruh Penganggaran Partisipatif Terhadap Budget Slack dengan Sikap sebagai Variabel Moderating - Anggia Dini Syahrir (InFestasi, 2017)
This study examines the effects of participative budgeting to the budget slack to be moderated by the attitude. This study used a sample of 140 individuals ranging from Head of Work Unit (SKPD) and Head of the Southeast Sulawesi provincial government. The analytical method used in this study is Partial Least Square (PLS) with SmartPLS as a means of statistical tests. The results showed that participative budgeting significant negative effect on the budget slack. The higher participation in preparing the budget, budget slack generated would be lower. As for the attitude of participative budgeting strengthened the influence of the budget slack. This indicates that the participant is responsible for the task in hand in preparing the budget so the attitude is able to strengthen the influence of participatory budgeting to budget slack.